Penerapan Asas Hukum Dalam Pembentukan Peraturan Perundang-Undangan - Rokilah Rokilah; Sulasno Sulasno (Universitas Serang Raya, 2021)
Legal norms (legal norms, rechtnormen) actually regulate internal personal life (internal life) in a civilized and humanistic manner and also regulate interpersonal relationships in social processes. Legal principles can be in the form of a legal norm that is high in location and many things depend on it and the principle can just a norm. This study aims to determine the application of legal principles in statutory regulations; and to find out the application of other principles in the field of laws and regulations. The research method uses a qualitative normative juridical research method with data collection sourced from library research. Based on the nature of this research, it is an explanatory research, namely research that explains and strengthens a theory on the results of existing research. The results of the study show that legal principles are not concrete legal rules, but are the background of concrete and general or abstract regulations. In general, legal principles are not stated in the form of concrete regulations or in the form of articles, but the law cannot be understood without these principles and the application of other principles in accordance with the legal field of the relevant legislation, including: in criminal law, for example the principle of legality, the principle of presumption of innocence and in civil law, for example in contract law, among others: the principle of agreement, freedom of contract, and good faith.